Conformity of Intellectual Development and Constructivism Textbooks of Science-Based Physics - Choir, Ridha Amalila; Tiara , Siti Ike Nur Jannah; Rahmadinanti, Moza Oriana; Sakti, Adinda Nina Eka; Yulianto, Rany Angeline; Rizky, Amallia; Hermansyah, Moh. Dimas Feri; Mahardika, I Ketut; Subiki; Rohmah, Ima Ainur (Balai Publikasi Indonesia, 2025)
Most students need help understanding physics material, especially Newton's laws. This is due to the thought that physics material is complex and requires memorizing formulas. This study aims to make it easier for students to understand physics material through Scientific-Based Textbooks. The research method uses research and development, which is used to create teaching material products and test product effectiveness. This study uses four stages: defining, designing, developing, and disseminating. The results showed that the teaching materials made in the form of textbooks were valid according to the results of the validation instruments that the validator had validated. The validator instruments include the eligibility of textbooks in the form of material, presentation systematics, language, contextual aspects, accessibility, navigation, communication, display quality, and the overall function of the media. The results of the percentage of validators related to the language feasibility of the Physics Textbook show the average rate by the two validators, namely 88.3% and 85%. The resulting percentage is feasible because the validity coefficient is > 85%. These results indicate that the Scientific Based Physics Textbook can be used after revision